The Impact of Technology on the Legal System: Exploring How Technology is Changing the Way Laws are Created, Enforced, and Interpreted - Muhammad Babar Shaheen; Zulfiqar Husaain; Dr. Noreen Akhtar; Shoket Ali (Review Journal of Social Psychology & Social Works, 2025)
The use of technology in the legal framework has brought about changes in how laws are made, implemented and even applied. Some of the modern possibilities of using AI, big data analysis, and blockchain include legal research and analysis of cases, making decisions in courts, and implementing measures to combat crime. Even though these developments enhance productivity and convenience, issues about prejudice, privacy, and the application of human reasoning arise at the same time. The research method used to analyze the papers is an Integrative Literature Review (ILR) that involves cross-sectional Analysis from the identified secondary sources such as academic papers, legal reports and policy documents. Some of the topics include using artificial intelligence in legal research, using analytics in law enforcement, and the legal aspects of governance in using artificial intelligence applications. Some theories on how artificial intelligence is used in legal systems are retrieved from scholarly articles in peer-reviewed journals and government documents. This article reveals that using AI in legal research and working with cases increases their productivity in multiple ways. ODR platforms increase the availability of justice in a given society’s society, especially in the case of cross-border disputes. However, legal decision-making through AI entails important issues like bias, privacy, and ethical issues of accountability. Candor and legal supervision are required to avoid unfair justice decisions and potential threats associated with the abuse of mass surveillance. Thus, AI and digital technologies are useful in the legal system, while the responsibility of legal decisions should be with humans. Some regulatory measures, along with ethical AI governance and an open court system and judiciary, will be central to ensuring the fundamental rights and fairness of AI processes in the legal system.